Strategi Pengelolaan Manajemen Mutu Dalam Proses Pendidikan di Sekolah Lanjutan Tingkat Pertama - Riana, Dewi (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study investigates quality management strategies in the educational process in Junior High Schools (SLTP). Using a qualitative approach and case studies, this study aims to evaluate optimal practices that can improve the quality of education in junior high schools. The results show that successful strategies include policy development, careful planning, consistent implementation, continuous evaluation, and corrective actions based on the results of the evaluation. This finding highlights the importance of a shared commitment to maintain consistency and improve the quality of the learning process in junior high schools, as well as to develop managerial skills and support innovation in quality management. Keywords: Strategy, Management, Quality Management, Education, Junior High School